Perancangan Sistem Informasi Pengolahan Data Member Pada Rai Fitness Sukabumi - Yuri Yuliani; Yuri Rahayu; Robi Aziz Zuama; susilawati susilawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2021)
The processing of member data at Rai Fitness Sukabumi is still done manually and some problems in the data processing system used today include the data entry process that is less efficient and optimal and the recording of acceptance and addition of members is still not recorded and good. This final research method is to conduct research, observation, interviews with the Front Office Rai Fitness Sukabumi, and literature study. Then the system design is carried out using UML (Unified Modeling Language) Providing convenience for the Front Office in the process of inputting data on registration and adding members, facilitating the performance of the Front Office in making journals and reports on registration, and adding members. The establishment of a data recording application that is stored properly and neatly in one database. Information system design. Member data processing for registration and member extension aims to facilitate the Front Office in carrying out data processing on registration and addition of members. Report makers are needed faster than before, namely, presenting the report requires more time and accuracy. Keywords : Information System Design, Member Data Processing